Dental Sutures: Types, Techniques, and Their Role in Oral Surgery and Wound Healing - Nourah Nasser almalik,; Manal Abdullah Alshareef,; Afnan Faisal Abdullah Almalki,; Azhar Hussain Asiry,; Amany sami alFawzan,; Fatmah Fihan Albogami,; Haifa Abdulkader Bajunaid,; Abdulaziz Maged Marzog Almutair,; Mohammed ibrahim Aloqayfi,; Sali Ahmed Ibrahim Aljayzani,; Dhafer Mohammad Dhafer Alshehri,; Ashwag Moohmaed Alahmari, (International Journal of Medical Toxicology and Legal Medicine, 2024)
Dental sutures are an integral component of oral surgery, facilitating tissue approximation, wound closure, and stabilization during the healing process. They are used in various dental procedures, including extractions, periodontal surgeries, and implant placements. Sutures not only provide mechanical support to the wound but also protect it from contaminants, reducing the risk of infection and promoting faster recovery. The choice of suture material and technique is crucial, as it impacts tissue reactions, healing time, and the likelihood of complications. Sutures are broadly classified as absorbable or non-absorbable, natural or synthetic, and monofilament or multifilament, with each type suited for specific clinical scenarios. Advances in suture technology, such as antibacterial coatings and barbed sutures, have further improved surgical outcomes by reducing infection risks and enhancing efficiency. However, complications such as tissue reactions, infections, wound dehiscence, knot-related issues, and patient noncompliance highlight the importance of proper suture selection and technique. This article provides a comprehensive overview of dental sutures, including their types, materials, techniques, roles in wound healing, and potential complications, aiming to enhance understanding and improve clinical outcomes in dental practice.